Retreatment experience with Glecaprevir/Pibrentasvir (G/P) for hepatitis C infection in patients failing first-line direct-acting antiviral agents. - Orestes J. Cobos-Quevedo; Ximena E. Cuenca-Avila; Leonardo S. Juárez-Chávez; Mauricio Castillo-Barradas; Enrique Carrera-Estupiñan; José L. Pérez-Hernández; María F. Higuera-De la Tijera (Annals of Hepatology, 2024)
Introduction and Objectives: First-line direct-acting antiviral agents (DAAs) achieved a sustained viral response (SVR) in >95%, failure to follow the scheme is rare and the option of retreatment with sofosbuvir/velpatasvir/voxilaprevir does not exist in our setting, therefore although G/P is considered an alternative, it is the only available option. There are few reports evaluating it; due to this, we describe the frequency and characteristics of patients with failure to first-line DAA schemes and the result of retreatment with G/P during the period from January 2017 to January 2023 in 3 tertiary hospital centers. Materials and Patients: The intentional search for cases with failure to achieve SVR with first-line DAAs was carried out in 2 Mexican reference centers and one Ecuadorian center during the period from January 2017 to January 2023. Characteristics and results of patients treated with the scheme were documented. of G/P. No conflict of interest was reported by the researchers. Results: From a total of 2,397 HCV-infected patients treated with the first-line DAA scheme, without cirrhosis or with compensated cirrhosis, a total of 9 patients presented virological failure, the average age was 52.4 years, five women and four men, of these, six patients had fibrosis grade F4, 3 of them F1, the predominant genotype was 1a, the initial regimens were SOF/VEL or SOF/LED in the majority, only one case used Paritaprevir/Ritonavir/Ombitasvir/Dasabuvir + Ribavirin, all the patients re-treated with G/P had SVR at 12 weeks, no resistance profile was routinely performed, adverse effects were mild, and were reported in 22.2% of the total, none of them abandoned treatment. Conclusions: First-line DAAs are effective; virological failure in our sample is lower (0.37%) than reported in the literature. G/P is an effective and safe scheme for retreatment of patients with failure without cirrhosis or with compensated cirrhosis (100% response in our study), without serious adverse effects, which makes it possible to eliminate and meet the WHO 2030 goals.